The mediating influence of local cultures on the relationship between factors of safety risk perception and Risk-Taking behavioural intention of construction site workers. (January 2022) - Owusu Danso, Frederick; Adinyira, Emmanuel; Manu, Patrick; Agyekum, Kofi; Kwaku Ahadzie, Divine; Badu, Edward
Highlights: How local culture (LC) affects risk-taking behavioural intention (RTBI) is studied. LC mediates the relationship between personal safety attitude and RTBI. A culture-based intervening policy for safety education and training is needed. Abstract: Safety risk perception and local cultures are two determinants that influence site workers' risk-taking behavioural intention during construction. The former and its influences are empirically valid, while the latter remains descriptive. How these two determinants relate to influencing site workers' risk-taking behavioural intention remains unexplored. This study examines the influence of local cultures on the relationship between safety risk perception and the risk-taking behavioural intention of site workers. Following an extensive literature review, the study identified 33 behavioural measures consisting of local cultures and safety risk perception and modified for questionnaire design using the Theory of Planned Behaviour. The study collected data from a randomised 96 site workers across multiple construction sites in Ghana. The Partial Least-Squares of Structural Equation Model was employed to analyse the data obtained from the survey. The developed structural path model confirmed the hypotheses that the personal safety attitudes of site workers have a substantial effect in influencing their risk-taking behavioural intention and that four local cultures mediate this influence, namely: beliefs in God for protection; revering attitudes towards elders; valued opinions of family members; and having faith in God to overcome safety risks. These results explain why site workers in a developing country context may engage in risk-taking behaviours during construction. The study supports the need for a culture-based intervening policy for construction safety education and training with roles for religious institutions and communal leaders.